Commercial Photoshop retouching : in the studio - Honiball, Glenn (O'Reilly, 2005)
For both Mac and Windows PC users, Photoshop CS2 is the market leader and industry standard for commercial bitmap image manipulation. Also known as the "digital dark room," Photoshop is the unparalleled tool of choice among graphics professionals and hobby photographers alike. Written by 20-year photo retouching veteran Glenn Honiball, Commercial Photoshop Retouching: In the Studio is the only book to deliver advice for the photographer and artist working with Photoshop CS 2 in a real world commercial environment. Honiball offers incomparable technical and artistic guidance for professionals, g.